Highlight Test Code: Visualizing the Co-Evolution of Test and Production Code in Software Repositories - Miranda, Charles; Avelino, Guilherme; Santos Neto, Pedro (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2025: Anais do XXXIX Simpósio Brasileiro de Engenharia de Software, 2025)
The asynchronous evolution of test and production code can compromise software quality and maintainability. However, identifying and analyzing such co-evolution dynamics remains a complex task, often hindered by the lack of scalable tools and comprehensive visualizations. This paper presents Highlight Test Code, a web-based platform for analyzing the co-evolution of test and production code in open-source repositories. The platform implements a multi-stage pipeline encompassing repository mining, time series generation, clustering, and statistical correlation. It is built upon a curated dataset of 526 GitHub repositories across six programming languages. Highlight Test Code offers visual analytics and AI-generated insights that assist users in identifying test evolution patterns, evaluating co-evolution levels, and understanding their relationship with maintenance activities and project characteristics. The tool enables researchers and practitioners to assess testing practices at scale. Video link: https://youtu.be/U29eEg_gXXM . Software License: General Public License (GPL).